PENERAPAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI BENTUK ALJABAR - Raykrismonita, Mirawati; Anita, Ika Wahyu; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to determine the improvement of students' mathematics learning outcomes by applying a problem based learning approach to algebraic form of material. The method used in this research is classroom action research (CAR) which was carried out in one of the junior high schools in the Cimahi area. This research was carried out for two cycles, with the techniques used were observation, test questions, and also documentation. The subjects of this class action research were teachers and students of SMP class VII which consisted of 22 people. The increase in student learning outcomes is reviewed based on the results of working on individual test questions. The questions are given before and after the algebraic form material is delivered. Based on the results of the study, it was shown that learning mathematics by applying a problem based learning approach to algebraic form material could improve student learning outcomes.